Aplikasi Metoda Geolistrik Konfigurasi Wenner-Alpha Untuk Eksplorasi Batubara - Farma, Rakhmawati (Jurnal Pilar Sains, 2003)
Geoelectrical method uses variation of resistivity values to study subsurface geology structure, thereforeit can be applied to explore groundwater, pollution of groundwater, and geothermal exploration. In thisstudy, a physical modeling was built in the laboratory, that is used to resistivity measurement on coalsamples. The measurements employ Wenner-Alpha configuration. The result of the tests show that coallayer can be detected based on resistivity variation. The semi-antharasite sample showed higherresistivity than bituminous sample. This result is in accondance with the fact that semi antharsite drierthan bituminous sample.